Meta-Analysis the Effects of Working Duration and Working Condition on Satisfaction in Health Workers in Hospital - Kurniawan, Aditya; Tamtomo , Didik; Murti, Bhisma (Journal of Health Policy and Management, 2024)
Background: Job satisfaction of health workers in hospitals is one of the important points for motivation and increasing work effectiveness, high job satisfaction can improve the performance of health workers and patient satisfaction. However, low job satisfaction results in fatigue and a tendency to increase the turnover of health personnel which will exacerbate the condition of health facilities, especially in hospitals. The aim of the research is to conduct a meta-analysis of previous studies that have been conducted on the effect of working time and working conditions on the job satisfaction of health personnel in hospitals. Subjects and Method: This study is a meta-analysis with PICO. Population: health personnel. Intervention: long working time and good working conditions. Comparison: Working time is short and working conditions are bad. Outcome: job satisfaction. The articles used in this study were obtained from four databases, namely PubMed, Google Scholar, Science Direct, SpringerLink, BMJ, Garuda, SINTA, and the National Library of Indonesia. Keywords used to search for articles “Working Hours” OR “Working Hours Long” AND “Working Conditions” OR “Working Conditions Good” AND “Job Satisfaction” AND “Health Workers” AND “Multivariate”. The articles used were those which are full text in English from 2014 to 2023. Articles were selected using the PRISMA flowchart and analyzed using the application (RevMan) 5.3. Results: A total of 17 cross-sectional study articles from Belgium, Canada, China Denmark, Ethiopia, Israel and Switzerland. Based on the analysis, health personnel with long working hours reduced job satisfaction 0.47 times compared to health workers with low working hours and this was statistically significant (aOR=0.47; 95% CI=0.12 to 0.92; p=0.030). Health workers with safe working conditions increased job satisfaction 2.75 times compared to health workers with unsafe working conditions and this was statistically significant (aOR=2.75; 95% CI=1.59 to 4.78; p=0.003). Conclusion: Long working hours reduce the job satisfaction of health personnel and good working conditions increase the job satisfaction of health personnel. Keywords: Working Time, Working Conditions, Job Satisfaction, Health Personnels Correspondence: Aditya Kurniawan. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36A, Surakarta 57126, Central Java, Indonesia. Email: akur88@gmail.com Mobile: +6285642088532